Risk Assessment and Management for Potential Living Kidney Donors: The Role of “Third-Party” Commission - Tattoli, Lucia; Santovito, Davide; Raciti, Ida Marina; Scarmozzino, Antonio; Di Vella, Giancarlo (Frontiers in Public Health, 2022)
Living kidney donation is the most common type of living-donor transplant. Italian guidelines allow the living donations from emotionally related donors only after clear and voluntary consent expressed by both the donor and the recipient involved. Living donation raises ethical and legal issues because donors voluntarily undergo a surgical procedure to remove a healthy kidney in order to help another person. According to the Italian standards, the assessment of living donor-recipient pair has to be conducted by a medical “third party”, completely independent from both the patients involved and the medical team treating the recipient. Starting from the Hospital “Città della Salute e della Scienza” of Turin (Italy) experience, including 116 living kidney donations, the Authors divided the evaluation process performed by the “Third-Party” Commission into four stages, with a particular attention to the potential donor. Living donation procedures should reflect fiduciary duties that healthcare providers have toward their patients, originating from the relationship of trust between physician and patient. In addition to that, the social implications are enormous if one considers the worldwide campaigns to promote public awareness about organ donation and transplantation, and to encourage people to register their organ donation decisions. The systematic process proposed here can be a tool that proactively reduces and controls the risks of coercion, organ trafficking, vitiated consent, insufficient weighting of donative choice, that could arise especially in donors involved in living kidney donation.